Foundation's Financial Management in the Perspective of Sharia Management - Muhammad Sadri (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The aim of this research is to determine the financial management of the Daruttahfidz An-Nur Mataram Foundation and analyze the management of the Daruttahfidz Foundation from a Sharia Management perspective. This research uses a qualitative approach with observation methods, interviews and documentation. The data sources in this research are the founders, supervisors, administrators, as primary data sources and teachers, student guardians, the community as secondary data sources. The results of the research are: first, the financial management of the Daruttahfidz An-Nur Mataram Foundation in general comes from donors, the government, the community and student guardians. Meanwhile, its use is predominantly used for the construction and repair of Daruttahfidz An-Nur Mataram Foundation facilities. Second, from a Sharia perspective, the financial management of the Daruttahfidz An-Nur Mataram Foundation from its source is in accordance with Sharia views, while the use of Daruttahfidz An-Nur Mataram Foundation funds has been used on objects that are in accordance with sharia views and in accordance with statutory views. The implications of the results of this research can be a reference material for both the government and institutions to pay attention to non-formal institutions being developed professionally and provided with appropriate assistance.